De perspectiefgerichte benadering - Markus Altena Davidsen (Religie & Samenleving, 2022)
In late 2019, the Dutch Expert Centre Worldview and Religion in Secondary Education (Expertisecentrum Levensbeschouwing en Religie in het Voortgezet Onderwijs; LERVO) tasked a group of teachers and teacher trainers to work out a national curriculum for the subject area ‘worldview and religion’ (levensbeschouwing en religie). In this article, I outline the progress made so far. In the first section of the article, I discuss the general educational vision of LERVO that we have developed in dialogue with Gert Biesta’s theoretical pedagogy, Wolfgang Klafki’s theory of Bildung, and Fred Janssen’s ‘perspectives approach’ (perspectiefgerichte benadering). The second part of the article presents a new framework for the national curriculum, consisting of nine perspectives on worldview and religion (e.g., the meaning-making and phenomenological perspectives), and three additional learning lines focused, respectively, on dimensions of worldviews and religions, important traditions, and societal challenges.